Detection of Pesticide Residues in The Canal Irrigation System of The Upper Mekong Delta, Cambodia - Sombath Keo; Khy Eam Eang; Chanvorleak Phat; Sereyvath Yoeun; Leakkhina Meak; Kong Chhuon; Sylvain Massuel (Indonesian Journal of Limnology, 2022)
Pesticide refers to all chemical compounds which are mainly used in agriculture to control pests and weeds. In many developing countries, the increasing use of pesticides is due to agricultural activities for intensification purposes. The potential consequences for the environment, health and biodiversity are difficult to anticipate, as the presence of pesticides is difficult and rarely monitored. This is the case in the upper Mekong delta in Cambodia where many irrigation systems are being developed. The aim of the study is to provide a preliminary assessment of the situation by looking for the presence of pesticides in the water within a representative irrigation system. Water samples were collected in canals, river, irrigated rice field and groundwater in both dry and wet seasons. Solid-phase extraction (SPE) and gas chromatography-mass spectrometry (GC-MS) methods were used to purify and analyze the samples. Among 37 pesticides used by farmers and detectable, 6 were found in water. Paclobutrazol and propiconazole are moderately hazardous, hexaconazole is slightly hazardous, fluquinconazole presents acute toxicity and azoxystrobin is unlikely to present acute hazard. Hexaconazole and paclobutrazol are classified as highly persistent in water, while others are slightly to moderately persistent. Pesticides were found mostly in groundwater but they were found in the canals and rice field only in dry season. This means that pesticides may accumulate in the aquifer while the flooding has a flushing effect on pesticides. Further analyses should be extended to a bigger scale and be continued monitoring.